Randomized trial of allergen‐induced asthmatic response in smokers and non‐smokers: effects of inhaled corticosteroids. Issue 10 (15th September 2015) - Cahn, A.; Boyce, M.; Mistry, S.; Musani, N.; Rambaran, C.; Storey, J.; Ventresca, P.; Michel, O.
Summary: Background: It is thought that asthmatics who smoke cigarettes respond less well to inhaled corticosteroid (ICS) therapy than asthmatics who do not smoke. Objective: To evaluate the effects of smoking on allergen‐induced airway responses in asthmatics treated with ICS. Methods: Randomized, double‐blind, crossover study evaluating twice daily fluticasone propionate (FP) 100 μg, FP 500 μg and placebo, for 7 days, on allergen‐induced asthmatic responses in 18 non‐smoking and 17 smoking atopic asthmatics (NCT01400906). At 1 h post‐morning dose on Day 6, forced expiratory volume in 1 sec (FEV1 ) was measured up to 10 h post‐challenge. Exhaled nitric oxide (eNO), induced sputum cell counts, and responsiveness to methacholine were assessed the following day. Results: The late asthmatic response (LAR) was suppressed by FP in smokers and non‐smokers; with placebo, the LAR was also attenuated in smokers versus non‐smokers (adjusted mean minimum change in FEV1 (L) over 4–10 h [95% CI] in non‐smokers: placebo −1.01 [1.31, 0.70], FP 100 μg −0.38 [0.54, 0.22], FP 500 μg −0.35 [0.54–0.22]; and in smokers: placebo −0.63 [0.84, 0.43]; FP 100 μg −0.44 [0.65, 0.23]; FP 500 μg −0.46 [0.59–0.32]). The Early AR was suppressed by FP treatment in non‐smokers, but was not impacted in smokers. The reduction in methacholine hyperresponsiveness after FP was greater in non‐smokers (1.5‐ and twofold doubling dose difference from placebo after FP 100 μg and FP 500 μg) than smokers (1.0 and 1.3 difference, respectively). Allergen‐induced increases in eNO and sputum eosinophils were lower in smokers than non‐smokers and were suppressed in both groups by FP. Conclusion and Clinical Relevance: Allergen‐induced LARs were of a similar amplitude in both smoking and non‐smoking atopic asthmatics at the end of ICS treatment, but attenuation of the LAR in smokers was only partly associated with ICS treatment. The marked attenuation of the LAR observed in smokers in the absence of ICS treatment is a novel observation.